ANALISIS STRUKTUR PASAR SAPI MADURA DI DESA DEMPO BARAT, KECAMATAN PASEAN, KABUPATEN PAMEKASAN - Salsabilah, Namira; Widodo, Slamet (JURNAL AGRIBISAINS, 2022)
Cattle farming has been considered necessary in community life. The marketing of cattle in Dempo Barat Village, Pasean District, Pamekasan Regency is still mostly done through mediators, which means the price obtained by farmers is not optimal. The aim of this research is to analyze the market structure of Madura Cattle in West Dempo Village. The method of analysis in this research is descriptive and quantitative. The market structure is analyzed by explaining the number of market participants, barriers to market entry, and market information. The market structure is analyzed using a market concentration approach by measuring market share, HHI (Hirschman Herfindahl Index), and CR4 (Concentration Ratio for the Biggest Four). Based on the research results, the market structure of Madura Cattle in West Dempo Village leads to an oligopoly market with loose concentration. Farmers are advised to sell cattle directly to traders in the market to increase revenue. To help farmers get better deals, the government needs to make rules about how marketing institutions work.